Design and Fabrication of a Garbage Lifting Equipment for Collecting Plastic Waste in Lake Matano, Indonesia (Journal of Namibian Studies : History Politics Culture, 2023)
A pile of plastic waste has been seen across the shore of Lake Matano. This has become the result of local people’s bad behavior for years for not throwing their garbage in its place. The waste has been carried by the stream and forms a disturbing plastic pile along the shore which had raised some environmental concerns over this behavior. Therefore, this requires serious attention particularly from the community and local government for a solution. There have been some actions taken for trying to solve it, however, a similar pile is still found in some hotspots. There has been some limitation to those actions, for example, to reach areas under the water that has already been mixed with mud for a long time and those which has been stacked under the houses of the local’s residents. This research aims to design and Fabrication a garbage collection device in Lake which aims to facilitate the cleaning of the lake, especially garbage that is difficult to reach from the shores of the Matano Lake. A small boat equipped with a conveyor system working with solar energy was successfully made with a size of 3740x2200x800 (L x W x H). A test was done specifically on the weight of the boat which was approximately 198.47kg, with a buoyancy force of 606,53 kg, Then the volume for the hull part would sink whenever reach its capacity of 78.89%. A test was also carried out on the movement of the boat. By attaching a gasoline engine with a capacity of 5.5 HP, we obtain data that the equipment can run at a maximum speed of 2.66 km/hour.